Criminology of war in the current realities and the need for its development in Ukraine - Sokurenko, Vitalii; Krykun, Viacheslav; Zhuravlova, Zoria; Brusakova, Oksana; Kritsak, Ivan; Savchuk, Tetiana (DIXI, 2022)
Many Ukrainian citizens have moved to safer regions of our country or gone abroad. This has led to rethinking of human values, crystallization of attitudes towards death, in particular, whether we are ready to “lay down our lives for our friends” (John 15:13), and thus to exercise the highest expression of love for our neighbour. Our grandfathers and great-grandfathers, who survived famine and other shocks, were most afraid of war. The main wish after 1945 was a peaceful sky on the Earth. What spiritual power and strength was laid in the words of peace? However, seventy years of freedom gradually contributed to the loss of this feeling. The human heart has become petrified, and people have become cruel and hateful to each other, when for certain reasons global circumstances condone war. No one could have thought that our northern neighbor would destroy cities and villages, critical infrastructure of our country, with such force and pace. History and time will give answers to all the questions and condemn the criminals.
Keywords: development; protection; territorial integrity; Ukraine; criminology